2015
DOI: 10.1007/s00018-015-1997-9
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulation of the intestinal epithelium

Abstract: The intestinal epithelium is an ideal model system for the study of normal and pathological differentiation processes. The mammalian intestinal epithelium is a single cell layer comprised of proliferative crypts and differentiated villi. The crypts contain both proliferating and quiescent stem cell populations that self-renew and produce all the differentiated cell types, which are replaced every 3 to 5 days. The genetics of intestinal development, homeostasis, and disease are well defined, but less is known a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 206 publications
(279 reference statements)
0
22
0
Order By: Relevance
“…In particular, morphogenesis of lung epithelial barriers continues throughout normal postnatal development, characterized by ongoing septation and epithelialization of the lung 104 . Consequently, perturbation of barrier morphogenesis in childhood may have a lasting effect on adult epithelium via alteration of developmental programs and epigenetic reprogramming at developmental checkpoints 105107 . Multiple lines of evidence now implicate active re-engagement of morphogenetic programs in adult disease, typically not seen in adult homeostatic tissue 108110 .…”
Section: Mechanisms Of Barrier Defectsmentioning
confidence: 99%
“…In particular, morphogenesis of lung epithelial barriers continues throughout normal postnatal development, characterized by ongoing septation and epithelialization of the lung 104 . Consequently, perturbation of barrier morphogenesis in childhood may have a lasting effect on adult epithelium via alteration of developmental programs and epigenetic reprogramming at developmental checkpoints 105107 . Multiple lines of evidence now implicate active re-engagement of morphogenetic programs in adult disease, typically not seen in adult homeostatic tissue 108110 .…”
Section: Mechanisms Of Barrier Defectsmentioning
confidence: 99%
“…Recent work has suggested that microbiota-directed epigenomics is a central mechanism driving intestinal development [74,75]. Genome-wide examination of the postnatal methylome revealed microbiota-dependent increases in DNA methylation in intestinal stem cells within maturation-associated genes that positively correlated with increased gene expression [76].…”
Section: Epigenomic Pathways Directed By the Microbiota Maintain Intementioning
confidence: 99%
“…According to the epigenetic progenitor model of cancer epigenetic alterations affecting tissue specific differentiation are the prominent mechanism by which epigenetic changes cause cancer . However, there is still a lack of information about the precise changes occurring in the epigenetic state during differentiation processes of the intestinal epithelium .…”
Section: Discussionmentioning
confidence: 99%